Challenges to professional teacher development through workplace culture management - Khairiah Khairiah; Alfauzan Amin; Muassomah Muassomah; Mira Mareta; Sulistyorini Sulistyorini; Mirna Yusuf (International Journal of Evaluation and Research in Education (IJERE), 2024)
The implementation of professional teacher development in Indonesia has been lacking. Many teachers continue to underperform, as evidenced by their workplace behaviors that violate the ethics of their profession. Workplace culture has contributed significantly to, and been detrimentally affected by, this lack of professionalism. Using a qualitative approach, this study seeks to explore the forms, factors, and implications of these challenges for the management of workplace culture. Teachers are simultaneously the objects and key informants of this research, which was conducted through observation of secondary-level madrasas spread throughout Bengkulu Province, Indonesia, as well as interviews with 15 teachers. This study identifies three main challenges: i) teachers have difficulty accessing professional training; ii) teachers cannot readily continue their educations; and iii) teachers have trouble writing and publishing academic works. These challenges are caused by a multitude of factors, primarily the lack of the funding, facilities, and infrastructure for professional development, as well as teachers limited digital literacy, and result in a workplace culture where initiative goes unrewarded, discipline is lacking, and teachers are unmotivated. As such, this study recommends significant improvements to the structure, culture, and infrastructure of educational institutions, thereby allowing teachers to overcome the challenges that hinder their professional development.